PRE-ECLAMPSIA: RISK FACTORS, PREVENTION, AND IMPACT ON MATERNAL-FETAL HEALTH - Izabela da Silva Simões; Eriadne Ágda Kiepert; Luiz Fernando de Souza Aquino; Sorhaylla Assunção Castanho D’Orazio; Thais Souza dos Reis Facini; Wanessa Ferreira Cabocolino da Silva (Artefactum - revista de estudos interdisciplinares, 2026)
Preeclampsia represents one of the most complex and challenging conditions of human pregnancy, characterized as a multisystem disorder triggered by the presence of the placenta and manifested primarily by new-onset hypertension accompanied by significant proteinuria or target-organ dysfunction after the twentieth week of gestation. This study aims to comprehensively analyze the determining risk factors, molecular pathogenetic mechanisms, evidence-based prophylactic measures, and clinical outcomes affecting the maternal-fetal unit. The methodology employed is based on a critical, in-depth narrative review of recent obstetric medical literature and consensus statements from international and national scientific societies. The etiopathogenesis is rooted in the primary failure of uterine spiral artery remodeling by extravillous trophoblast cells, resulting in chronic placental ischemia and the subsequent excessive release of anti-angiogenic factors—notably sFlt-1 and soluble endoglin—into the maternal circulation. This cascade culminates in systemic endothelial dysfunction, vasospasm, platelet activation, and altered vascular permeability, predisposing the patient to severe complications such as eclampsia, HELLP syndrome, and intrauterine growth restriction. It is concluded that early screening in the first trimester, timely prophylactic intervention with acetylsalicylic acid, and rigorous monitoring are indispensable pillars for mitigating global rates of maternal and perinatal morbidity and mortality.